Characteristics of the femoral tunnel of anatomical and isometric single bundle anterior cruciate ligament reconstruction: a modeling analysis based on quadrant method and anatomical landmarks - Li Yin; Dongfa Liao; Qingyun Xie; Jinbiao Liu; Bing Deng (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To investigate the anatomical features of the femoral tunnel in anatomical and isometric single-bundle ACL reconstruction. Method Thirty-two 3-dimensional knee models were reconstructed based on CT scan (average age: 26.5 ± 6.7 years, 18 males and 14 females, 17 left and 15 right). Multiple anatomical landmarks were identified. Virtual femoral tunnels were created at the deep and high portion of ACL footprint, close to the lateral intercondylar ridge to achieve best anatomy and isometry, simulating an anteromedial portal reconstruction. Anatomical features of the femoral tunnels were analyzed. The position of the femoral tunnel was quantified by the distance to anatomical landmarks and using quadrant methods. The spatial angles, length and outer opening of the femoral tunnels were also evaluated. Results Acceptable tunnels were created in all models. The center of femoral tunnel was slightly higher than the apex of deep cartilage, near the deep one-third point across the shallow-deep dimension of the lateral femoral condyle. Using the quadrant method, the tunnel was located at 28.4% ± 2.2% and 22.2% ± 3.6%, parallel and perpendicular to the Blumensaat line, respectively. The spatial angles of the tunnel were 40°, 33.5° ± 4.1° and 38.2° ± 4.4° on the sagittal, transverse, and coronal planes, respectively. The average tunnel length was 34.8 mm ± 3.8 mm. The outer opening of the tunnels was located at the posterior one-third of the femoral metaphysis. Conclusion The anatomical and isometric positioning of the femoral tunnel can be achieved through anteromedial portal with satisfied tunnel characteristics. The apex of deep cartilage may be used as an anatomical reference for tunnel positioning. When drilled at appropriate orientation, favorable tunnel length, integrity and position of the outer opening can be obtained.